Efektivitas Nanopartikel Bayam Merah (Amaranthus Tricolor L.) Terhadap Kadar Hormon Prolaktin dan Produksi Asi Pada Ibu Menyusui - Nawang Setyoningrum; Krisdiana Wijayanti; Arwani Arwani (Jurnal Ners, 2026)
Exclusive breastfeeding period is a vulnerable period for breast milk (ASI) sufficiency to meet infant nutritional needs. Red spinach (Amaranthus tricolor L.) contains galactagogue compounds that have the potential to increase breast milk production by increasing prolactin levels. Objective: To determine the effectiveness of red spinach (Amaranthus tricolor L.) nanoparticles on prolactin levels and breast milk production in breastfeeding mothers. Method: This study employed a quasi-experimental design with a pretest–posttest control group design. The sample consisted of 32 breastfeeding mothers divided into two groups, with 16 participants in the intervention group and 16 in the control group, recruited from Mangunsari Primary Health Center and a private midwifery clinic (BPM Ibu Alam), as well as Sidorejo Kidul Primary Health Center, Salatiga. The intervention group received red spinach nanoparticles at a dose of 250 mg for 14 days, while the control group received breastfeeding education. Breast milk production was assessed indirectly using infant weight gain, whereas prolactin hormone levels were measured using the ELISA method. Data were analyzed using the Wilcoxon test, Paired Sample T Test, Mann–Whitney test, Repeated Measures ANOVA, and Independent t-test. Results: Administration of red spinach nanoparticles significantly increased prolactin levels in the intervention group (p = 0.013), whereas no significant change was observed in the control group (p = 0.955). Infant weight gain occurred in both the intervention and control groups (p<0.000); however, no statistically significant difference was found between the two groups. Conclusion: Red spinach nanoparticles at a dose of 250 mg administered for 14 days were effective in increasing prolactin levels in breastfeeding mothers. This intervention has the potential to support breast milk production, as indicated by infant weight gain, although no significant difference was observed compared to the control group